Personality and metabolic dysfunction in young adulthood: A cross-sectional study. (March 2019) - Sutin, Angelina R; Stephan, Yannick; Terracciano, Antonio
This research used the National Longitudinal Study of Adolescent to Adult Health ( N  = 15, 359; age range 25–34) to examine the cross-sectional relation between personality and four components of metabolic syndrome (elevated glucose, blood pressure, cholesterol, and waist circumference) and a metabolic risk index in young adulthood. Consistent with research on older adults, higher Neuroticism and lower Conscientiousness were associated with greater risk of metabolic dysfunction; Agreeableness, however, was unrelated to it. The relation between personality and metabolic health may unfold across the lifespan, with the association between Neuroticism/Conscientiousness and metabolic dysfunction starting early and the association with Agreeableness emerging at older ages.